Green Belts Vis-a-vis Environmental Pollution - Pokhriyal, T. C.; Nautiyal, S. (Indian Forester, 1991)
The paper deals with the effective role of green belts in mitigating the pollution problems of urban environment. Useful tree species for developing green belts at different climatic zones have been suggested. The multiple role of these plantations located in the neighbourhood of industrial complexes is emphasized.